2021
DOI: 10.1180/mgm.2021.11
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of fumarolic anhydrous copper sulfate minerals during successive hydration/dehydration

Abstract: Hydration processes of primary anhydrous minerals as well as dehydration of the hydrated phases are relevant not only for answering geochemical and petrological questions, but are also interesting in the context of the theory of the ‘Evolution of minerals’. Our study of the evolution of anhydrous exhalative sulfates in hydration and dehydration processes has demonstrated the complexity of the processes for a number of minerals from the active high-temperature fumaroles of Tolbachik volcano (chalcocyanite Cu(SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…upon hydration-dehydration cycles. Yet, our studies of such processes for selected copper sulfate minerals indicate that these are very complicated (Siidra et al, 2021a), include numerous steps and are not always reversible even for initially single-phase specimens. It is however very likely that these studies, extended into more complex systems, will produce even more intricate and intriguing architectures, compositions and possibly properties.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…upon hydration-dehydration cycles. Yet, our studies of such processes for selected copper sulfate minerals indicate that these are very complicated (Siidra et al, 2021a), include numerous steps and are not always reversible even for initially single-phase specimens. It is however very likely that these studies, extended into more complex systems, will produce even more intricate and intriguing architectures, compositions and possibly properties.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The obtained new compound shows the probability of detecting such compounds (especially for copper-containing ones) in the zones of fumaroles exposed to intense atmospheric precipitation. Alkali copper sulfates are known to form multiple hydrated "offsprings" during exposure to moist air (Siidra et al, 2021b).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Testasicca et al (2016)] but with little success. During the last three years, we have found that A 2 Cu(SO 4 ) 2 (A = Na, K, Rb) compounds constitute a complex morphotropic series which consists of at least five different structural modifications [-, -,and -phases, see Siidra et al (2021a)]. This work completes the structural series from the large-cation side adding the "-type for A = Cs (Table 5).…”
Section: Cs 2 Cu(so 4 )mentioning
confidence: 65%
“…It is worth noting that most known alkali copper sulfate representatives are structurally based on threedimensional copper sulfate frameworks (Borisov et al, 2021). ISSN 2052-5206 While several examples of Rb-Cu sulfates have been recently reported (Siidra et al, 2021a), anhydrous sulfates of caesium with copper, as well as with cobalt, remain mostly unaddressed; to the best of our knowledge, no reliable data have been reported. In order to fill this gap and to elucidate the effect of alkali cation size on the structural architectures of two relatively numerous series, A I 2 Cu(SO 4 ) 2 and A I 2 M II 2 (SO 4 ) 3 , we have undertaken this study.…”
Section: Introductionmentioning
confidence: 99%